How dyspepsia, gastroesophageal reflux symptoms, and overlapping symptoms affect quality of life, use of health care, and medication - a long-term population based cohort study. (3rd July 2021) - Klausen, Katrine Mie; Bomme Høgh, Maria; David, Marc; Schaffalitzky de Muckadell, Ove B.; Hansen, Jane Møller
Abstract: Background and aim: The prevalence of gastroesophageal reflux symptoms (GERS) and dyspepsia is high. Overlapping of GERS and dyspepsia has been described to affect quality of life. However, studies are few. This long-term population-based study evaluates how GERS, dyspepsia, and overlapping symptoms, affect quality of life, and the use of health care and medication. Methods: This study presents data for the control group of the randomised population study, HEP-FYN. At baseline 10, 000 individuals, aged 40–65 years, received questionnaires at baseline and after 1, 5 and 13 years. The questionnaire included questions regarding demographics, use of health care resources, gastrointestinal symptoms (the Gastrointestinal Symptom Rating Scale (GSRS)), and the Short-Form 36-Item Health Survey (SF-36) to assess quality of life. Results: Complete data was available for 4.403 individuals at 13-year follow-up. Of these 13.6% reported GERS only, 11.6% dyspepsia only, and 27.1% overlapping symptoms during follow-up. Individuals reporting overlapping symptoms had compared to individuals reporting GERS only or dyspepsia only more visits at general practitioner (last year:16.7% vs. 8.5% vs. 12.3%), more sick leave days (last month: 4.3% vs. 2.9% vs 0.7%), used more ulcer drugs (last month: 30.5% vs 16.4% vs 9.4%). In addition, individuals with overlapping symptoms reported a lower quality of life in all eight dimensions of SF-36 compared to individuals with GERS alone or dyspepsia alone. Conclusions: Overlapping symptoms was associated with lower quality of life scores and substantial use of health-care resources. Having solely GERS affected quality of life and health care use least.